Metaverse Dakwah: Rekonstruksi Ruang Sakral dan Pengalaman Religius dalam Ibadah Virtual - Iim Said Sabiq (IKHBAR: Jurnal Ilmu Dakwah dan Komunikasi, 2026)
The evolution of Web 3.0 technology has birthed the Metaverse, an immersive digital reality blurring the lines between the physical and the virtual. This phenomenon presents both new challenges and opportunities for dawah activities and religious practices. This study aims to analyze how sacred space is reconstructed within the Metaverse environment and how it affects the religious experience of users (avatars). Using a qualitative method with a digital phenomenology approach and literature review, this research explores the ontology of worship in cyberspace. The results indicate that the Metaverse is capable of reconstructing sacred space through symbolic manipulation and audio-visual atmosphere, yet it faces theological challenges regarding the validity of ritual worship (ibadah mahdhah) which requires physical presence (ittihad al-majlis). Psychologically, the Metaverse offers a "telepresence" experience that can trigger spiritual emotions but risks reducing worship to mere aesthetic simulation. Dawah in the Metaverse is effective as an educational tool (manasik) and narrative propagation, but cannot fully replace physical rituals. This article recommends a hybrid approach in contemporary dawah: utilizing the Metaverse for engagement and education, while maintaining physical sanctity for core rituals.